POTONGAN HARGA, PENATAAN PRODUK DAN ATMOSFER TOKO DAMPAKNYA PADA KEPUTUSAN PEMBELIAN TIDAK TERENCANA KONSUMEN ALFAMART - Juniarsini, Ni Nengah Mega; Wibawa, I Gede Jaya Satria; Yanti, Ni Nyoman Suli Asmara (Institut Agama Hindu Negeri Gde Pudja Mataram, 2023)
Impulse buying decision is a form of consumer behavior that occurs suddenly without going through the planning process. This type of consumer behavior often occurs but is rarely realized and noticed. Many factors can trigger impulse buying decisions, such as price discounts, display product, and store atmosphere. The purpose of this research is to find out how the effect of price discounts, display product, and store atmosphere on impulse buying decisions of Alfamart consumers in Mataram City. 90 respondents were selected as the sample for this study, using purposive sampling as the sampling method. The data for this study were obtained through questionnaires distributed by online media using the help of the Google form. Multiple linear regression is a data analysis method that is used with the help of SPSS 25 software. This study obtained results indicating that price discounts, product arrangement, and store atmosphere partially or simultaneously influence impilse buying decisions. Based on the results of this study, Alfamart should pay more attention to the discounts given, as well as display product, as well as the level of comfort in the store, so as to maximize the effect of price discounts, display product and store atmosphere on consumer impulse buying decisions.